A method for preparing catalyst for removing non-methane total hydrocarbon from coke oven flue gas by precipitation
Patent Information
- Application Number
- CN202611042971.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]针对现有焦炉烟气非甲烷总烃治理中,贵金属催化剂成本高、耐硫性差,以及常规非贵金属催化剂低温活性不足、制备过程中组分分布不均、微观结构难以调控等技术难题,本发明的目的在于提供一种用于焦炉烟气非甲烷总烃催化氧化的复合金属氧化物催化剂及其制备方法
(1)工艺新颖,组分微观分布精准:本发明首创“pH梯度调控”策略,通过非线性程序化控制pH平缓上升,克服了Mn-Ce-Co体系因溶度积差异导致的沉淀分层难题,实现了多金属离子的有序分级沉淀与原子级均匀掺杂;
Smart Images

Figure CN122895004A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of atmospheric pollution control and environmental catalytic materials technology, specifically relating to a method for preparing a catalyst for removing non-methane total hydrocarbons from coke oven flue gas by precipitation. Background Technology
[0002] Coke oven flue gas, as a typical industrial waste gas in the iron and steel and coking industries, has an extremely complex composition. It not only contains high concentrations of particulate matter, sulfur oxides and nitrogen oxides, but also non-methane total hydrocarbons (NMHC) with large concentration fluctuations and complex components, mainly including benzene series compounds, polycyclic aromatic hydrocarbons and alkanes. These pollutants are not only important precursors of photochemical smog and secondary organic aerosols, but also pose a serious threat to the environment and human health.
[0003] Among existing treatment technologies, catalytic oxidation is widely used due to its low energy consumption, high purification efficiency, and lack of secondary pollution. The performance of the catalyst directly determines the treatment effect and operational economy. Although noble metal catalysts, represented by platinum and palladium, possess excellent low-temperature ignition activity, their high resource cost and extreme sensitivity to residual sulfides in flue gas, which easily lead to irreversible chemisorption and sulfur poisoning, severely limit their industrial application in long-term coke oven flue gas treatment. In contrast, transition metal oxides have become ideal materials to replace noble metals due to their low cost and good resistance to poisoning. In particular, manganese (Mn)-based oxides have attracted much attention due to their variable valence states and excellent redox cycle capabilities. To further overcome the shortcomings of insufficient low-temperature activity and poor thermal stability of single manganese oxides, researchers often introduce cerium (Ce) and cobalt (Co) as promoters to construct multi-component composite oxides, attempting to improve catalytic performance through Ce's oxygen storage capacity and Co's electronic regulation effect.
[0004] However, existing preparation processes severely limit the full potential of the Mn-Ce-Co multi-component system, mainly facing two major technical bottlenecks: "uneven component distribution" and "uncontrollable nanostructure". Specifically, due to the significant differences in the solubility product constants of the three metal ions Mn, Ce, and Co, their pH ranges for hydrolysis precipitation do not overlap. In traditional constant pH or rapid co-precipitation processes, each component is prone to stepwise precipitation or encapsulation precipitation based on its own hydrolysis characteristics, leading to phase separation at the microscale. This makes it difficult to form a uniform solid solution structure and severely weakens the electronic synergistic effect between metals. In addition, existing morphology control methods usually adopt a stepwise process of "precipitation-filtration and washing-rehydrothermal treatment". This non-in-situ treatment method not only causes the loss of key structure-guiding ions in the mother liquor, but also easily leads to the aggregation or structural collapse of precursors during washing and transfer. It is impossible to use the hydrothermal environment to induce the formation of specific nano-hierarchical structures with high specific surface area (such as nanoflowers, nanowires, etc.) in situ, resulting in insufficient exposed active sites of the catalyst, making it difficult to maintain efficient and stable catalytic activity under the complex conditions of low temperature, sulfur content, and water content in coke oven flue gas.
[0005] Therefore, developing a novel preparation process that can precisely control the precipitation kinetics of multi-component metals and achieve in-situ structural assembly is key to breaking through the current performance bottleneck of non-precious metal catalysts. Summary of the Invention
[0006] To address the technical challenges in existing coke oven flue gas non-methane total hydrocarbon treatment methods, such as the high cost and poor sulfur resistance of precious metal catalysts, and the insufficient low-temperature activity, uneven component distribution, and difficulty in controlling the microstructure of conventional non-precious metal catalysts, this invention aims to provide a composite metal oxide catalyst for the catalytic oxidation of non-methane total hydrocarbons in coke oven flue gas and its preparation method. This invention aims to prepare a Mn-Ce-Co ternary composite oxide catalyst with high specific surface area, high and low temperature activity, and excellent sulfur and water resistance through precise precipitation kinetic control and in-situ structural assembly.
[0007] To achieve the above objectives, the present invention provides a method for preparing a catalyst for removing non-methane total hydrocarbons from coke oven flue gas by precipitation, comprising the following steps: S1: Dissolve soluble manganese salt, cerium salt and cobalt salt in a solvent to form a mixed precursor solution; S2: Under stirring conditions of 300-800 rpm, in a constant temperature water bath of 25-60℃, a precipitant is added dropwise to the mixed precursor solution in a preset program gradient, so that the pH value of the reaction system gradually increases from below 5 to 9-11 within 1-3 hours. After stirring and aging for 1-2 hours, a slurry is obtained. S3: The slurry obtained in step S2 is subjected to hydrothermal treatment at a temperature of 150-220℃ for 8-36 hours; S4: The slurry after hydrothermal treatment is separated by filtration. The separated solid is washed alternately with deionized water and anhydrous ethanol until the filtrate is neutral. Then it is dried at 80-120℃ for 8-24 hours and calcined at 350-550℃ to obtain the catalyst.
[0008] A composite metal oxide catalyst for the catalytic oxidation of non-methane total hydrocarbons in coke oven flue gas has the chemical formula MnaCexCoyO2+δ, where a, x, and y are mole fractions satisfying a+x+y=1, and 0.4≤a≤0.7, 0.2≤x≤0.5, and 0.05≤y≤0.2; δ is the non-stoichiometric number of oxygen, calculated using the formula: 2×(2+δ)= a·V Mn +x·V Ce +y·V Co (where V) Mn V Ce V Co The values are (the average oxidation states of Mn, Ce, and Co in the catalyst), -0.5 ≤ δ ≤ 0.5; the catalyst has a three-dimensional nanoflower structure, which is self-assembled from nanosheets with a thickness of 5-15 nm; the catalyst has a catalytic conversion rate of no less than 95% for toluene at a concentration of 500 ppm at 280 °C.
[0009] The preferred mole fractions a, x, and y are: a = 0.5, x = 0.4, y = 0.1; the specific surface area of the catalyst is 150-220 m². 2 / g, average pore size 5-12nm, total pore volume 0.3-0.6cm³ 3 / g. The industrial waste gas is coke oven flue gas, mainly containing benzene compounds, polycyclic aromatic hydrocarbons, and volatile organic compounds of alkanes.
[0010] In step S1, the soluble manganese salt, cerium salt, and cobalt salt are manganese nitrate, cerium nitrate, and cobalt nitrate, respectively; the solvent is deionized water; and the total concentration of metal ions in the mixed precursor solution is 0.2-1.0 mol / L.
[0011] The precipitant in step S2 is selected from one or a combination of sodium carbonate, sodium bicarbonate, sodium hydroxide, ammonia, or urea, and the concentration of the precipitant solution is 0.5-2.0 mol / L.
[0012] The "gradient addition according to a preset program" in step S2 refers to: using a precision peristaltic pump to control the flow rate of the precipitant, so that the pH value of the reaction system changes with time t in a linear function pH=k·t+b or an S-shaped nonlinear function, where k is a constant, to induce Ce 3+ Mn 2+ and Co 2+Based on the differences in their solubility products, orderly fractional coprecipitation is carried out.
[0013] The hydrothermal treatment in step S3 is carried out in a closed high-pressure reactor with a slurry filling degree of 60%-80% and a self-generated pressure of 1.0-3.0 MPa. The hydrothermal treatment process does not involve filtration and separation, and directly utilizes the co-precipitation mother liquor environment to induce the precursor to self-assemble into nanosheet structures.
[0014] The calcination in step S4 is carried out in a static air atmosphere or oxygen atmosphere, with a heating rate of 1-5℃ / min and a constant temperature calcination time of 3-5 hours.
[0015] Application of composite metal oxide catalysts in the treatment of industrial waste gas containing non-methane total hydrocarbons.
[0016] The beneficial effects of this invention are: (1) Novel process and precise microscopic distribution of components: This invention pioneered the "pH gradient control" strategy, which uses nonlinear programmed control to gradually increase pH, overcoming the problem of precipitation stratification caused by the difference in solubility product in the Mn-Ce-Co system, and realizing the orderly hierarchical precipitation and atomic-level uniform doping of multi-metal ions. (2) Unique structure and excellent low-temperature activity: The in-situ assembly process of "direct hydrothermal without washing" was adopted to induce the generation of a three-dimensional nanoflower structure with a high specific surface area by utilizing the mother liquor environment. This structure exposes a wealth of active sites, and combined with the strong electronic synergistic effect between ternary metals, it can achieve a catalytic conversion rate of more than 95% for toluene at a low temperature of 280℃; (3) Excellent resistance, low cost and easy to promote: The special hierarchical nanostructure endows the material with excellent hydrophobicity and physical barrier effect, and exhibits excellent stability under the complex coke oven flue gas conditions containing water and sulfur. Moreover, the present invention uses inexpensive non-precious metals, without the need to load expensive platinum and palladium, which greatly reduces the cost and has great prospects for industrial application. Attached Figure Description
[0017] Figure 1 Flowchart of a pH gradient controlled hydrothermal co-precipitation method for preparing catalysts to remove non-methane hydrocarbons from coke oven flue gas Detailed Implementation
[0018] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0019] This invention elaborates on the technical solution through specific embodiments to more clearly demonstrate its advantages and features. It should be noted that the embodiments are merely illustrative and do not constitute a limitation on the scope of protection of this invention. Any reasonable adjustments or equivalent substitutions made by those skilled in the art to the implementation details and forms of the technical solution without departing from the core idea of this invention should be considered to fall within the scope of protection of the claims of this invention.
[0020] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0021] The performance evaluation involved in this invention was conducted on a fixed-bed microreactor, and the specific test conditions are as follows: 1. Reactant gas: simulated coke oven flue gas, toluene concentration of 500 ppm, balance gas is air; 2. Test conditions: Catalyst loading was 200 mg (40-60 mesh particles), and gas hourly space velocity (GHSV) was set to 30,000 h⁻¹. -1 ; 3. Activity evaluation index: The temperature-programmed reaction was carried out in the range of 100-400℃, and the temperatures at which the toluene conversion rate reached 50% and 90% were recorded, denoted as T. 50 and T 90 ; 4. Resistance test: Under constant temperature of 280℃, 5% water vapor and 50ppm sulfur dioxide were introduced into the feed gas and run continuously for 100 hours to examine the retention of conversion rate. Example 1
[0022] This embodiment illustrates Mn 0.5 Ce 0.4 Co 0.1 O 2-δ The preparation process of the -1 nanoflower catalyst includes the following steps: S1: Weigh 6.275g of manganese nitrate (Mn(NO3)2·4H2O), 8.680g of cerium nitrate (Ce(NO3)3·6H2O), and 1.455g of cobalt nitrate (Co(NO3)2·6H2O), dissolve them in 100mL of deionized water, and stir until completely dissolved to obtain a mixed metal salt solution A; Separately weigh 10.60g of anhydrous sodium carbonate (Na2CO3), dissolve it in 100mL of deionized water, and prepare a 1.0mol / L precipitant solution B; S2: Place solution A in a 40℃ constant temperature water bath. Under magnetic stirring at 500 rpm, add solution B dropwise using a programmable peristaltic pump. Set the flow rate of the peristaltic pump so that the dropping rate increases linearly with time. Control the pH value of the reaction system to increase linearly from the initial 4.0 to 10.0 within 2.0 hours. Stop dropping when the pH reaches 10.0. Continue stirring and aging for 30 minutes to obtain the slurry. S3: Transfer the slurry obtained in the above steps directly into a 200mL stainless steel high-pressure reactor lined with polytetrafluoroethylene, with a filling degree of about 65%. After sealing, place it in an oven and perform hydrothermal treatment at 180℃ for 24 hours. S4: After the reactor cools naturally, the solid is separated by centrifugation. The filter cake is washed three times each with deionized water and anhydrous ethanol, alternating between the two methods. The filter cake is dried at 100℃ for 12 hours, then placed in a muffle furnace and calcined at 450℃ for 4 hours under air atmosphere at a rate of 2℃ / min to obtain the finished catalyst Mn. 0.5 Ce 0.4 Co 0.1 O 2-δ -1. Example 2
[0023] This embodiment illustrates Mn 0.6 Ce 0.3 Co 0.1 O 2-δ The preparation process of the -1 nanoflower catalyst includes the following steps: S1: Weigh 7.530g of manganese nitrate (Mn(NO3)2·4H2O), 6.510g of cerium nitrate (Ce(NO3)3·6H2O), and 1.455g of cobalt nitrate (Co(NO3)2·6H2O), dissolve them in 100mL of deionized water, and stir until completely dissolved to obtain a mixed metal salt solution A; Separately weigh 10.60g of anhydrous sodium carbonate (Na2CO3), dissolve it in 100mL of deionized water, and prepare a 1.0mol / L precipitant solution B; S2: Place solution A in a 40℃ constant temperature water bath. Under magnetic stirring at 500 rpm, add solution B dropwise using a programmable peristaltic pump. Set the flow rate of the peristaltic pump so that the dropping rate increases linearly with time. Control the pH value of the reaction system to increase linearly from the initial 4.0 to 10.0 within 2.0 hours. Stop dropping when the pH reaches 10.0. Continue stirring and aging for 30 minutes to obtain the slurry. S3: Transfer the slurry obtained in the above steps directly into a 200mL stainless steel high-pressure reactor lined with polytetrafluoroethylene, with a filling degree of about 65%. After sealing, place it in an oven and perform hydrothermal treatment at 180℃ for 24 hours. S4: After the reactor cools naturally, the solid is separated by centrifugation. The filter cake is washed three times each with deionized water and anhydrous ethanol, alternating between the two methods. The filter cake is dried at 100℃ for 12 hours, then placed in a muffle furnace and calcined at 450℃ for 4 hours under air atmosphere at a rate of 2℃ / min to obtain the finished catalyst Mn. 0.6 Ce 0.3 Co 0.1 O 2-δ -1. Example 3
[0024] This embodiment illustrates Mn 0.5 Ce 0.4 Co 0.1 O 2-δ The preparation process of the -2 nanometer flower catalyst includes the following steps: S1: Weigh 6.275g of manganese nitrate (Mn(NO3)2·4H2O), 8.680g of cerium nitrate (Ce(NO3)3·6H2O), and 1.455g of cobalt nitrate (Co(NO3)2·6H2O), dissolve them in 100mL of deionized water, and stir until completely dissolved to obtain a mixed metal salt solution A; Separately weigh 10.60g of anhydrous sodium carbonate (Na2CO3), dissolve it in 100mL of deionized water, and prepare a 1.0mol / L precipitant solution B; S2: Place solution A in a 40℃ constant temperature water bath. Under magnetic stirring at 500 rpm, add solution B dropwise using a programmable peristaltic pump. Set the flow rate of the peristaltic pump so that the dropping rate increases linearly with time. The flow rate is slow in the first 1.5 hours, so that the pH value only rises from 4.0 to 6.0. In the next 0.5 hours, the flow rate is increased so that the pH value rises rapidly from 6.0 to 10.0. The total dropping time is still 2.0 hours. When the pH reaches 10.0, stop dropping and continue stirring and aging for 30 minutes to obtain the slurry. S3: Transfer the slurry obtained in the above steps directly into a 200mL stainless steel high-pressure reactor lined with polytetrafluoroethylene, with a filling degree of about 65%. After sealing, place it in an oven and perform hydrothermal treatment at 150℃ for 36 hours. S4: After the reactor cools naturally, the solid is separated by centrifugation. The filter cake is washed three times each with deionized water and anhydrous ethanol, alternating between the two methods. The filter cake is dried at 100℃ for 12 hours, then placed in a muffle furnace and calcined at 450℃ for 4 hours under air atmosphere at a rate of 2℃ / min to obtain the finished catalyst Mn. 0.5 Ce 0.4 Co 0.1 O 2-δ -2. Comparative Example 1
[0025] This comparative example uses the traditional constant pH coprecipitation method to prepare Mn. 0.5 Ce0.4 Co 0.1 O 2-δ A catalyst having the same elemental loading as in Example 1 includes the following steps: S1: Weigh 6.275g of manganese nitrate (Mn(NO3)2·4H2O), 8.680g of cerium nitrate (Ce(NO3)3·6H2O), and 1.455g of cobalt nitrate (Co(NO3)2·6H2O), dissolve them in 100mL of deionized water, and stir until completely dissolved to obtain a mixed metal salt solution A; Separately weigh 10.60g of anhydrous sodium carbonate (Na2CO3), dissolve it in 100mL of deionized water, and prepare a 1.0mol / L precipitant solution B; S2: Prepare 200 mL of deionized water as the base solution and heat it to 40 °C. Add solutions A and B simultaneously dropwise to the base solution while running them in parallel. Control the dropping rate of sodium carbonate using an online pH meter to maintain the pH of the reaction system at 10.0 at all times. S3: Transfer the slurry obtained in the above steps directly into a 200mL stainless steel high-pressure reactor lined with polytetrafluoroethylene, with a filling degree of about 65%. After sealing, place it in an oven and perform hydrothermal treatment at 180℃ for 24 hours. S4: After the reactor has cooled naturally, the solid is separated by centrifugation. The filter cake is washed three times each with deionized water and anhydrous ethanol. The filter cake is dried at 100°C for 12 hours, then placed in a muffle furnace and calcined at 450°C for 4 hours under air atmosphere at a rate of 2°C / min to obtain the control sample catalyst. Comparative Example 2
[0026] This comparative example uses the traditional impregnation method to prepare Mn. 0.5 Ce 0.4 Co 0.1 O 2-δ A catalyst having the same elemental loading as in Example 1 includes the following steps: S1: Weigh 3.44g of commercial nano cerium dioxide (CeO2) powder as a carrier; weigh 6.275g of manganese nitrate (Mn(NO3)2·4H2O) and 1.455g of cobalt nitrate (Co(NO3)2·6H2O), dissolve them in 10mL of deionized water, and prepare a high-concentration mixed impregnation solution; S2: Add the impregnation solution dropwise to the CeO2 carrier, continuously grind and stir for 30 minutes, let it stand at room temperature for 12 hours, and then dry it at 100℃; S3: It was then placed in a muffle furnace and heated to 450°C at 2°C / min in air atmosphere, and calcined for 4 hours to obtain the comparative sample catalyst.
[0027] Table 1 Catalyst Removal Performance Test Example 1 185.6 225 248 99.2% Example 2 168.2 232 260 96.5% Example 3 192.4 228 255 98.1% Comparative Example 1 110.5 268 315 62.5% Comparative Example 2 65.4 285 340 45.2% As shown in Table 1, T in Example 1 90 The temperature is much lower than that of Comparative Example 1 (315℃), which indicates that by controlling the linear pH gradient, precipitation stratification caused by the difference in solubility product of Mn, Ce, and Co is effectively avoided, forming a uniform solid solution structure and significantly improving the low-temperature activity. Compared with the simple physical impregnation method of Comparative Example 2, the catalyst prepared by the co-precipitation-hydrothermal method of this invention has stronger intermetallic interactions and therefore exhibits better redox performance. In Example 2, appropriately increasing the Mn content slightly reduced the activity, but it remained at a high level, indicating that 5:4:1 was the optimal ratio. In Example 3, using exponential gradient and low-temperature long-term hydrothermal treatment, the highest specific surface area was obtained, and the activity was comparable to that of Example 1, demonstrating that the process parameters have a certain degree of adjustment flexibility.
[0028] The above description is merely a few preferred embodiments of the present invention and is not intended to limit the scope of protection of the present invention. It should be noted that those skilled in the art can make various modifications, equivalent substitutions, or improvements to the above embodiments without departing from the core ideas and technical principles of the present invention. Any such changes and modifications made within the spirit and principles of the present invention should be considered as included within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a catalyst for removing non-methane total hydrocarbons from coke oven flue gas by precipitation, characterized in that, Includes the following steps: S1: Dissolve soluble manganese salt, cerium salt and cobalt salt in a solvent to form a mixed precursor solution; S2: Under stirring conditions of 300-800 rpm, in a constant temperature water bath of 25-60℃, a precipitant is added dropwise to the mixed precursor solution in a preset program gradient, so that the pH value of the reaction system gradually increases from below 5 to 9-11 within 1-3 hours. After stirring and aging for 1-2 hours, a slurry is obtained. S3: The slurry obtained in step S2 is subjected to hydrothermal treatment at a temperature of 150-220℃ for 8-36 hours; S4: The slurry after hydrothermal treatment is separated by filtration. The separated solid is washed alternately with deionized water and anhydrous ethanol until the filtrate is neutral. Then it is dried at 80-120℃ for 8-24 hours and calcined at 350-550℃ to obtain the catalyst.
2. A composite metal oxide catalyst for the catalytic oxidation of non-methane total hydrocarbons in coke oven flue gas, characterized in that, The chemical formula of the catalyst is Mn a Ce x Co y O 2+δ Where a, x, and y are mole fractions, satisfying a + x + y = 1, and 0.4 ≤ a ≤ 0.7, 0.2 ≤ x ≤ 0.5, and 0.05 ≤ y ≤ 0.2; δ is the non-stoichiometric coefficient of oxygen, calculated using the formula: 2 × (2 + δ) = a·V Mn +x·V Ce +y·V Co (where V) Mn V Ce V Co The values are (the average oxidation states of Mn, Ce, and Co in the catalyst), -0.5 ≤ δ ≤ 0.5; the catalyst has a three-dimensional nanoflower structure, which is self-assembled from nanosheets with a thickness of 5-15 nm; the catalyst has a catalytic conversion rate of no less than 95% for toluene at a concentration of 500 ppm at 280 °C.
3. The method for preparing a catalyst for removing non-methane total hydrocarbons from coke oven flue gas by precipitation according to claim 1, characterized in that, The soluble manganese salt, cerium salt, and cobalt salt mentioned in step S1 are manganese nitrate, cerium nitrate, and cobalt nitrate, respectively; the solvent is deionized water; and the total concentration of metal ions in the mixed precursor solution is 0.2-1.0 mol / L.
4. The method for preparing a catalyst for removing non-methane total hydrocarbons from coke oven flue gas by precipitation according to claim 1, characterized in that, The precipitant used in step S2 is selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, ammonia, or urea, and the concentration of the precipitant solution is 0.5-2.0 mol / L.
5. The method for preparing a catalyst for removing non-methane total hydrocarbons from coke oven flue gas by precipitation according to claim 1, characterized in that, The "gradient dripping according to a preset program" in step S2 refers to: using a precision peristaltic pump to control the flow rate of the precipitant, so that the pH value of the reaction system changes with time t in a linear function pH=k·t+b or an S-shaped nonlinear function, where k is a constant, to induce Ce 3+ Mn 2+ and Co 2+ Based on the differences in their solubility products, orderly fractional coprecipitation is carried out.
6. The method for preparing a catalyst for removing non-methane total hydrocarbons from coke oven flue gas by precipitation according to claim 1, characterized in that, The hydrothermal treatment in step S3 is carried out in a closed high-pressure reactor with a slurry filling degree of 60%-80% and a self-generated pressure of 1.0-3.0 MPa. The hydrothermal treatment process does not involve filtration and separation, and directly utilizes the co-precipitation mother liquor environment to induce the precursor self-assembly to form a nanosheet structure.
7. The method for preparing a catalyst for removing non-methane total hydrocarbons from coke oven flue gas by precipitation according to claim 1, characterized in that, The calcination in step S4 is carried out under a static air atmosphere or an oxygen atmosphere, with a heating rate of 1-5℃ / min and a constant temperature calcination time of 3-5 hours.
8. A composite metal oxide catalyst for the catalytic oxidation of non-methane total hydrocarbons in coke oven flue gas according to claim 2, characterized in that, The preferred mole fractions a, x, and y are: a = 0.5, x = 0.4, and y = 0.1; the specific surface area of the catalyst is 150-220 m². 2 / g, average pore size 5-12nm, total pore volume 0.3-0.6cm³ 3 / g.
9. A composite metal oxide catalyst for the catalytic oxidation of non-methane total hydrocarbons in coke oven flue gas according to claim 2, characterized in that, The industrial waste gas is coke oven flue gas, which mainly contains benzene compounds, polycyclic aromatic hydrocarbons and volatile organic compounds of alkanes.
10. The application of the composite metal oxide catalyst according to any one of claims 1-2 in the treatment of industrial waste gas containing non-methane total hydrocarbons.